Age-Energy Tradeoff of Truncated ARQ Retransmission With Receiver Diversity - Grybosi, Jorge Felipe; Rebelatto, Joao Luiz; Moritz, Guilherme Luiz; Li, Yonghui (IEEE wireless communications letters, 2020)
In this letter, we evaluate the age-energy tradeoff of a network composed of a single Internet-of-Things (IoT) end-device (ED) that has randomly generated status updates to transmit to an access point (AP). More specifically, we elaborate on a recently proposed truncated automatic repeat request (TARQ) scheme by considering that the AP is provided with multiple antennas, operating either under the selection combining (SC) or the maximum ratio combining (MRC) techniques. Our results indicate that the proposed schemes, which we refer to as TARQ-SC and TARQ-MRC, provide a better age-energy tradeoff when compared to TARQ, being capable of achieving lower age-of-information (AoI) and energy consumption simultaneously.